An Efficient Route towards Quinazolinone Derivatives via I2/DMSO-Promoted Oxidative Decarboxylation of α-Amino Acids and Subsequent Oxidative Annulation Reaction - Samanta, Surya Kanta; Bera, Mrinal K. (Synthesis, 2023)
An efficient and straightforward strategy to synthesize a wide range of quinazolinone derivatives from commercially inexpensive 2-aminobenzamides and various amino acids via molecular iodine promoted oxidative decarboxylation of α-amino acids, followed by oxidative cyclization reaction, is revealed. Operational simplicity, consistent yield, functional group tolerance and sustainability are the other noteworthy features of the reaction. A large number of quinazolinone derivatives were conveniently prepared employing the current strategy. The synthesis of other related heteroarenes, such as benzoxazole and benzothiazole derivatives, following the same reaction conditions broadens the scope of the method.
Keywords: iodine; quinazolinones; amino acids; decarboxylation; dimethyl sulfoxide; oxidation